CHARACTERISTICS OF THE DAILY DIETARY STATE OF MALE PATIENTS WITH PSORIASIS IN THE WINTER SEASON - Nizom Jumakulovich Ermatov; Dilshod Bakhtiyarovich Khajiev (Innovate Conferences, 2025)
Psoriasis is a chronic immune-mediated inflammatory skin disease characterized by red, itchy rashes, most often occurring on the wrists, knees, scalp and lower back, but can occur on any surface of the skin, and negatively affects the quality of life of patients and ruins their lives, disrupts their mental and psychological state, and in some cases causes family conflicts, leading to death and a threat to their own life.